"Cantata para louvor e glória", de Cleide Dorta Benjamim: preparo para a execução - Vieira, Gerônimo Brito (2015)
This study aims to document the preparation process for the implementation of "Cantata To Praise and Glory"(Cantata Para Louvor e Glória), composed in 1985 by composer Cleide Dorta Benjamin (1936 - ), in order to anticipate and address the possible difficulties faced by future conductors, singers and instrumentalists. Issues that relate to the chosen text as well as its structure and importance in the compositional process, are initially addressed through a brief presentation of the work. Consequently, by addressing every detail of the work, solutions to vocal and instrumental execution difficulties, as well as with the conducting gesture, are analyzed, identified and proposed. The work also presents a report that describes all the practical processes of preparation of the Cantata: reissue of the score; selection and profile of singers and instrumentalists; rehearsals; changes and adjustments to the score; and a brief interview with four singers and two musicians who participated in the process. The interaction with the composer throughout a significant part of the work, brings a notable increase of possible clarifications and idea development, enabling a coherent performance of the work.